2012
DOI: 10.1088/0031-8949/86/02/025402
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between striction forces in dielectrics and optically induced forces in transparent media

Abstract: Optically induced forces applied to a transparent optical medium, which is inserted in a closed plane optical resonator, are calculated by means of an analysis of the changes in the eigenfrequency and energy stored in the resonator at various positions of the medium. These forces are compared with striction forces applied to the medium considered as a dielectric placed in an alternate electrical field within the resonator. It is shown that the optically induced forces are equal to the striction forces. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It was shown that there are only two types of optically induced forces [17] under steady-state conditions. These are density forces arising in an inhomogeneous optical medium where its permittivity is changed in space and the electrostriction pressure which takes place in any medium.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that there are only two types of optically induced forces [17] under steady-state conditions. These are density forces arising in an inhomogeneous optical medium where its permittivity is changed in space and the electrostriction pressure which takes place in any medium.…”
Section: Introductionmentioning
confidence: 99%